Undercover bromance eaudiobook - Adams, Lyssa Kay (Bromance Book Club, 2020)
One of OprahMag.com’s Best Romances of 2020  Braden Mack thinks reading romance novels makes him an expert in love, but he’ll soon discover that real life is better than fiction.  Liv Papandreas has a dream job as a sous chef at Nashville’s hottest restaurant. Too bad the celebrity chef owner is less than charming behind kitchen doors. After she catches him harassing a young hostess, she confronts him and gets fired. Liv vows revenge, but she’ll need assistance to take on the powerful chef. Unfortunately, that means turning to Braden Mack. When Liv’s blackballed from the restaurant scene, the charismatic nightclub entrepreneur offers to help expose her ex-boss, but she is suspicious of his motives. He’ll need to call in reinforcements: the Bromance Book Club. Inspired by the romantic suspense novel they’re reading, the book club assists Liv in setting up a sting operation to take down the chef. But they’re just as eager to help Mack figure out the way to Liv’s heart. . .even though she’s determined to squelch the sparks between them before she gets burned.